MANAJEMEN NUTRISI PADA PASIEN POST OPERASI DI RSUP. R.D KANDOU MANADO - Sirait, Imelda (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2023)
Optimal nutrition is key to the maintenance of the entire wound healing phase in post-operative patients. Providing nutrition in the postoperative period can reduce complications, especially severe infections and in malnourished patients. In postoperative patients poor preoperative nutritional status has been associated with postoperative complications, increased mordibitas and mortality. The purpose of this community service program is to educate the public that nutrition management is very important in the wound healing process in postoperative patients at RSUP. Prof. Dr.R.D Kandou Manado. The method of carrying out the activity is to visit the Irina A Bawah Room specifically for post-operative patients at the hospital. Prof.Dr.R.D Kandou Manado and conducted education related to nutrition management for post-operative patients which was carried out on April 5, 2023 at 14.00 WITA – 15.00 WITA